Navigating Tensions: The Dynamic Growth of Preservice Teachers’ Critical Translingual Stance in Partnership with Refugee Children - Trautman, Katie; Corriston, Kelsie (International Electronic Journal of Elementary Education, 2026)
This comparative case study explores how two preservice teachers (PTs), working with recently arrived Afghan refugee students in a reading methods course, navigated and enacted critical translingual stances, despite the course’s absence of explicit translanguaging pedagogy. Framed by Critical Translingual Approach and Culturally Disruptive Pedagogy, this study analyzes the non-linear, situated development of two racially, ethnically, and linguistically different PTs’ ideological stances and pedagogical choices. Findings illustrate the tensions PTs experienced as they sought to recognize and affirm their students’ full linguistic and cultural repertoires while contending with normative language ideologies, conflicting expectations, and narrow views of literacy. The study highlights the importance of critical joy, relationship building, and oral storytelling as literacy practices, while also pointing to the need for deeper theoretical and experiential preparation in teacher education. We end with a call for teacher educators to embed justice-oriented approaches across the curriculum and to create and sustain ruptures that invite the confrontation of whiteness.